PHILOSOPHICAL ASPECT OF THE PROBLEM OF RATIO, RATIONAL AND IRRATIONAL IN THE SUBJECTS ECONOMIC BEHAVIOR - A. G. Avakyan-Forer (Концепт: философия, религия, культура, 2018)
The article is devoted to the analysis of the basic concepts of the behavioral economics. Based on the ideas of R. Easterlin and H. Leibenstein, the author investigates a ratio of the rational and irrational in the behavior of economic subjects. Besides, many of the problems of modern consumer society receive an explanation from the point of view of the N. Howe and W. Strauss generational theory. The article shows that the irrational behavior does not arise as a random deviation; in certain conditions it is capable to get the best of rational motivations. The ratio of rational and irrational in the behavior of economic subjects is associated with their psychological characteristics and is a reaction to the constantly increasing amount of information and the changing rules. It is about some kind of change in arrangement of accents when the place and the role of these two beginnings are considerably reconsidered. The behavioral economics in recent research have proved that preferences of economic subjects are more irrational, unpredictable; they are not always aimed at defending their own interests. It became obvious that the objective circumstances given from the outside are not able to explain properly the behavior of subjects of economic and their consequences. The ratio of irrational and rational behavior of economic subjects requires a new understanding. This circumstance is complicated by the fact that behavioral approach, in reality is inherent not only in the activities of an individual, but also in the development of firms, markets, regions. The article reveals deep motives of irrational behavior of economic subjects and shows the value of philosophical understanding of this problem for the further development of the behavioral economics theory.